Hierarchical porous hybrid chitosan scaffolds with tailorable mechanical properties - Sen, Tugce; Ozcelik, Berkay; Qiao, Greg G.; Ozmen, Mehmet Murat (ELSEVIER SCIENCE BV, 2017)
Hierarchical porous chitosan scaffolds were produced by combination of phase separation and ice templating methods. The resulting chitosan matrix was modified by post cross-linking using different concentrations of poly(ethylene glycol) diglycidyl ether (PEGDGE) to obtain novel hybrid hydrogel sponges with tailorable elasticity. Using this strategy, the elastic moduli of these sponges could be significantly altered between 0.1 and 2 MPa. The internal morphology of the sponges revealed a hierarchical pore structure ranging from large pores of between 20 and 70 mm to smaller pores of between 3 and 10 mm. Their pore structure and tunable elastic properties make these biomaterials attractive for tissue engineering applications. Crown Copyright (C) 2017 Published by Elsevier B.V. All rights reserved.
Keywords: Biomaterials; Scaffolds; Hydrogel; Hierarchical; Macroporous; Elasticity; FABRICATION; HYDROGELS; POLY(EPSILON-CAPROLACTONE); DESIGN; Materials Science; Physics